Empowerment of Weaving Groups in Developing Innovation and Creativity Through Product Diversification in the Sipatuo Business Group in Campalagian District - Kartika, Eka Dewi; Laitupa, Salma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Weaving activities carried out by housewives with the name of the weaving group ''sipatuo'' in Campalagian District at the initial observation amounted to 15 people. The knowledge and skills of weaving carried out by housewives in the sipatuo craftsman business were obtained because the skills were passed down from generation to generation. from family. This service activity provides contribution actually in the form of scientific knowledge and technique in making product-woven products and strategies the marketing also choosing the right raw materials in making woven products. Specifically on the partners of the shoe weaving business group as target partner of the West Sulawesi university service team. .